Sounds and hydrodynamics of polar active fluids - Geyer, Delphine; Morin, Alexandre; Bartolo, Denis (Nature materials, 2018)
Spontaneously flowing liquids have been successfully engineered from a variety of biological and synthetic self-propelled units 1 – 11 . Together with their orientational order, wave propagation in such active fluids has remained a subject of intense theoretical studies 12 – 17 . However, the experimental observation of this phenomenon has remained elusive. Here, we establish and exploit the propagation of sound waves in colloidal active materials with broken rotational symmetry. We demonstrate that two mixed modes, coupling density and velocity fluctuations, propagate along all directions in colloidal-roller fluids. We then show how the six material constants defining the linear hydrodynamics of these active liquids can be measured from their spontaneous fluctuation spectrum, while being out of reach of conventional rheological methods. This active-sound spectroscopy is not specific to synthetic active materials and could provide a quantitative hydrodynamic description of herds, flocks and swarms from inspection of their large-scale fluctuations 18 – 21 . Sound wave propagation is used to quantitatively describe the hydrodynamics of an active colloidal medium.